Role of heat shock protein in radiation-induced effect and related potential clinical application - Ying Xu; Wentao Hu; Guangming Zhou (Radiation Medicine and Protection)
Heat shock protein (HSP), as an intracellular chaperone, is significantly upregulated when cells are exposed to radiation and other stress environments, playing an important role in cell self-protection. This phenomenon not only provides a mechanism for normal tissues to resist radiation damage, but also provides a strategy for cancer cells to reduce their sensitivity to radiation and escape treatment. More research is needed to clarify the specific mechanism of HSP in radiotherapy and how to better use its biological effects for clinical individualized treatment. This paper reviews the biological effects of HSP under radiation and the latest research progress of combined radiation and HSP inhibitors or hyperthermia, in the hope of having a more comprehensive understanding of its mechanism in physiological processes such as cell survival, apoptosis, inflammation, immune response, as well as radiation response, which will help to enhance the therapeutic effect and to provide more effective and safer radiotherapy for cancer patients in the future.